Ultra-wideband chaotic optical communication based on electro-optic differential feedback loop - Yu, Meitong; Wang, Hongxiang; Ji, Yuefeng; Zhang, Yu (Optics communications, 2023)
A differential feedback electro-optical phase chaotic system is proposed to generate ultra-wideband optical chaos and realize high-speed long-distance chaotic communication. The nonlinear dynamics of this differential feedback loop are studied in detail. The numerical results show, firstly, in terms of chaos complexity, the highest permutation entropy of 0.993 and the largest spectral entropy of 0.945 are achieved. Regarding the key hiding, the time delay signature of phase chaos on both the autocorrelation function and delayed mutual information can be completely suppressed, so security can be guaranteed. Secondly, the maximum bandwidth of the radio spectrum is 46.75 GHz in the range of 50 GHz, and the minimum flatness is 1.62 dB/GHz. Finally, the reception of format-transparent messages can be realized by combining co-drive synchronization and coherent demodulation. The 50 GBaud QPSK signal can transmit 2400 km and the 25 GBaud 16 QAM signal can transmit 1500 km at an OSNR of 25 dB. This system realizes ultra-wideband high-complexity chaos and chaotic communication, which can greatly improve the security, transmission distance, and transmission rate of chaotic optical communication. •High complexity and ultra-wideband electro-optical differential feedback chaos generation.•The time delay signature (TDS) of the optical chaos is suppressed.•Chaotic synchronization based on laser co-drive injection.•High-speed and long-distance secure optical chaotic communication.